2019
DOI: 10.1039/c8sc03862g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic properties of hexanuclear cobalt sulfide superatoms via ligand substitution

Abstract: The electronic properties of the Co6S8L8 superatom can be tuned by changing its ligand composition while maintaining its electron count and closed shell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 53 publications
1
32
1
Order By: Relevance
“…Recently, photoelectron spectroscopy, photoabsorption spectroscopy, collision‐induced dissociation mass spectrometry, and ion‐mobility mass spectrometry have been applied to gain the intrinsic structure information in the absence of the external perturbation such as solvent and counter ion. [ 65,230,232,259–267 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, photoelectron spectroscopy, photoabsorption spectroscopy, collision‐induced dissociation mass spectrometry, and ion‐mobility mass spectrometry have been applied to gain the intrinsic structure information in the absence of the external perturbation such as solvent and counter ion. [ 65,230,232,259–267 ]…”
Section: Discussionmentioning
confidence: 99%
“…These materials exhibit larger dielectric constants than organic semiconductors with profound consequences for their excitedstate properties, such as the ability to exploit quantum confinement effects. A variety of such molecular clusters, often referred to as superatoms, has already been used for the formation of solid-state materials [14][15][16][17][18] . A special interest is thereby focused on the influence of the structure of the assembled materials onto their properties, possibly enabling the creation of materials with desired properties by design 19,20 .…”
mentioning
confidence: 99%
“…Recently, we have shown that the position of HOMO or LUMO in a variety of metal clusters can be tuned by using charge transfer ligands with electron-donating or accepting properties such as phosphine (PEt 3 , PMe 3 ), CO, CN as they bond and form surface dipoles. [41][42][43][44][45][46][47][48][49][50] We have also found that fused metal-chalcogenide clusters with unbalanced ligands may create intense internal electric fields that are ideal for separating electron-hole pairs in photon harvesting. 51 In this work, we have induced a diode-like shift in the conduction and valence level group of states on both sides of the bridged superatomic molecule by attaching N-ethyl-2-pyrrolidone (EP = C 6 H 11 NO) ligands on one of the PAl 12 clusters.…”
Section: Introductionmentioning
confidence: 95%